A BRIEF OVERVIEW OF COVID-19 DIAGNOSIS BY REAL-TIME RT-PCR (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
During the pandemic, key priorities included diagnosis, prevention, and elimination of the disease. Numerous test systems with varying levels of sensitivity were developed for diagnostic purposes. Among these systems, molecular-genetic assays hold a particularly important place, as they enable accurate identification of infectious agents. Within this approach, the most widely used method for diagnostic purposes in scientific research and clinical settings is real-time RT-PCR. In this work, we provide a brief overview of the real-time RT-PCR method. The fundamental principles of the method, its variants, as well as its advantages and limitations, are outlined.
Keywords: real-time RT-PCR, virus, SARS-CoV-2, method